The Development and Assesment Talent Mapping E-module for Elementary School - Jannah, Misbahul; Hayati, Zikra; Oviana, Wati (Universitas Islam Negeri Raden Intan Lampung, 2022)
The development of students' creativity should be adjusted to their talents so that teachers at schools need to have guidelines for mapping children's talents. This study is conducted to develop and assess the E-module on mapping the talents of elementary students in Aceh. The Design Development Research (DDR) research uses the Alessi and Trolip instructional design model involving 3 experts, 9 PGMI lecturers, and 15 MI teachers in three PTKINs in Aceh. The research instrument is a questionnaire that is analyzed by alpha and beta testing using descriptive analysis. The results of the alpha and beta assessments show that the mean assessment of MI experts, lecturers, and teachers is at a high stage (more than 4.0). Thus, it can be concluded that the talent mapping E-module for elementary students is suitable to use in elementary schools. For further research, it should be able to develop a talent mapping E-module for the high school level and able to be developed using learning technology in the form of E-learning.